Determination of Nutritional Habits and Physical Activity Levels of Healthcare Professionals: Nutrition and physical activity healthcare professionals - Tan, Çetin; Tan, Suriye; Erdoğan, Ramazan (Progress in Nutrition, 2020)
In this study, it was aimed to examine the nutritional habits and physical activity levels of healthcare professionals. 131 (67 women, 64 men) volunteer healthcare professionals working in health institutions in Elazığ participated in the study. “Personal Information Form” was used to determine the demographic information of the participants, “Nutritional Habits and Nutrition Information Levels” developed by Yücel (2015) to determine the nutritional habits and knowledge levels, and the “International Physical Activity Survey” short form was determined to determine the physical activity levels. SPSS package program was used to analyze the data. In the study, p